“Healing”: Pemahaman dan Praktiknya dalam Pariwisata Berdasarkan Konten Media Sosial TikTok - Wulandini, Indah (Gadjah Mada Journal of Tourism Studies, 2025)
This study examines the understanding and practice of healing in tourism activities in Yogyakarta, which is influenced by the social media platform TikTok. The phrase "healing" has gained popularity, frequently serving as a synonym for leisure and tourism, especially in the aftermath of COVID-19, as people pursue physical, mental, and emotional restoration. Employing a qualitative descriptive approach, interviews were carried out with 10 TikTok users, aged 18-24, to examine their perceptions of healing and their practices related to it in the context of tourism. The data indicate that the notion of healing is comprehended in three primary dimensions: mental health recovery, tourism, and rejuvenation. The study emphasizes that social media, particularly TikTok, has transformed the concept of healing into a fusion of emotional recovery and tourism, rendering it a crucial element in travel decisions. Yogyakarta has been a preferred locale for rejuvenation owing to its natural and cultural allure. This research enhances the existing literature on healing tourism by demonstrating the impact of digital trends on travel behavior and offering insights into the future of healing as a wellness practice and marketing instrument within the tourism sector.